Biological activity and LC-MS profiling of ethyl acetate extracts from Nitraria sibirica (Pall.) fruits. Issue 17 (2nd September 2018) - Gu, Dongyu; Yang, Yi; Bakri, Mahinur; Chen, Qibin; Aisa, Haji Akber
Abstract: Nitraria sibirica is a traditional Uighur medicine. This study was undertaken to investigate the bioactivity of N. sibirica fruit extract and to evaluate their chemical compositions. The ethyl acetate extract from N. sibirica fruits exhibited the potential antioxidant activity (SC50  = 30.17 ± 0.06 μg/mL) and protein tyrosine phosphatase 1B inhibitory activity (IC50  = 7.15 ± 0.03 μg/mL) in vitro . In order to investigate the active constituents in this extract, a LC-QTOF-MS/MS method was developed and established. A total of 28 compounds including seven cinnamic acids, nine benzoic acids and 12 flavonoids were identified or partially characterised according to the accurate mass and the characteristic fragment ions at low and high collision energy. Most of them were reported for the first time in this plant. Phytochemical profiles of the active extract will help the development and utilisation of N. sibirica in food and medicine. Abstract :